Transcriptome profiling of mouse brains with qkI-deficient oligodendrocytes reveals major alternative splicing defects including self-splicing - Darbelli, Lama (Sci Rep, 2017)
The qkI gene encodes a family of RNA binding proteins alternatively spliced at its 3′ end, giving rise to three major spliced isoforms: QKI-5, QKI-6 and QKI-7. Their expression is tightly regulated during brain development with nuclear QKI-5 being the most abundant during embryogenesis followed by QKI-6 and QKI-7 that peak during myelination. Previously, we generated a mouse conditional qkI allele where exon 2 is excised using Olig2-Cre resulting in QKI-deficient oligodendrocytes (OLs). These mice have dysmyelination and die at the third post-natal week. Herein, we performed a transcriptomic analysis of P14 mouse brains of QKI-proficient (QKI (FL/FL;-)) and QKI-deficient (QKI (FL/FL;Olig2-Cre)) OLs. QKI deficiency results in major global changes of gene expression and RNA processing with >1,800 differentially expressed genes with the top categories being axon ensheathment and myelination. Specific downregulated genes included major myelin proteins, suggesting that the QKI proteins are key regulators of RNA metabolism in OLs. We also identify 810 alternatively spliced genes including known QKI targets, MBP and Nfasc. Interestingly, we observe in QKI (FL/FL;Olig2-Cre) a switch in exon 2-deficient qkI mRNAs favoring the expression of the qkI-5 rather than the qkI-6 and qkI-7. These findings define QKI as regulators of alternative splicing in OLs including self-splicing.